TOOLKIT FOR IMPROVING FINANCIAL RESULTS IN THE SYSTEM FOR STRENGTHENING THE ECONOMIC SECURITY OF THE ENTERPRISE - DZERELEIKO, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article focuses on the relevance of planning and implementation of tools aimed at improving the financial condition and ensuring the economic security of the enterprise. The purpose of the study is to justify the tools for improving financial results in the system of strengthening the economic security of the enterprise.The method of planning and forecasting the volume and structure of the company's income is applied based on the calculation of break-even points, minimum profitability, resource-backed profit. Based on the financial and economic reporting data of the seven enterprises analyzed in the study, the income, expenses and performance indicators (initial data for calculating break-even) of the enterprises were determined. Indicators of critical limits of economic activity (income) of enterprises are calculated and given. The coefficients of deviation of the values of income at the point of resource-supported profit from the actual income of enterprises, as well as the coefficients of deviation of the actual volumes of income of enterprises from the income at the break-even point were determined. The directions and tools for improving financial results in the system of strengthening the economic security of the enterprise are substantiated. Areas, measures and structural subdivisions of realizing the potential of improving financial results in the system of strengthening the economic security of the enterprise have been determined.It has been established that the improvement of the company's financial results has a positive effect on the strengthening of all components of its economic security, including financial, intellectual and personnel, technical and technological, institutional and legal, marketing, logistics, information, security, etc. Improvement of financial results is achieved by increasing the company's income, as well as reducing (optimizing) its costs. In terms of increasing income, it is important to find all possible alternatives, both in terms of internal and external sources. In order to optimize the costs of the enterprise, it is appropriate to implement a balanced set of measures in the following directions: (1) rationalization of contingent and fixed costs, (2) reduction of the level of variable costs, (3) improvement of the system of stimulating the work of personnel, (4) ensuring technical and technological modernization of production and business -processes, (5) optimization of circulation costs.
Keywords: enterprise; economic security; financial component; financial position; tools and means of strengthening